The Role of Urban Agriculture Approach in Food Supply and Export Ability (Case Study of Neishabour in Iran) - Reza Mojtahedi, Mohammad (2021)
The growth of cities and the increase of urban population in recent years has caused many problems for the health of the environment and citizens. On the other hand, given that urbanism is inevitable, we must think of ways to reduce the pressure on nature by cities and improve economic and social indicators in cities. Urban agriculture will play an effective role in establishing a logical relationship between urban needs and improving the economic situation. In this research, the study of the role of urban agriculture from an economic point of view, especially in the field of food supply and export ability has been emphasized. The research method is descriptive-analytical and based on collecting survey data (field). The main research tool is a questionnaire. Its validity was confirmed by elites and its reliability was confirmed by completing 30 questionnaires through Cronbach's alpha at a level greater than 0.70. The study population was 264,375 citizens living in Neishabour. The sample size was determined by Cochran's formula equal to 384 people. The results showed that urban agriculture is significant in food supply and export ability at a level of less than 0.05. The city's agriculture can be effective in improving the export of organic products, fruits and vegetables, exports of ornamental and medicinal plants, branding of products, as well as in supplying fresh vegetables, providing healthy food, improving the quality of nutrition and protein. Urban agriculture has a significant level of less than 0.05 in urban development indicators such as improving the urban environment, improving employment, improving citizens' incomes, creating attractive urban spaces, rainwater consumption, etc. From the people's point of view, it is possible to cultivate crops such as peaches, Damask rose, poultry breeding, etc., according to the available spaces. The study of the role of urban agriculture through structural equations shows that the total effect is 0.81 and in total urban agriculture can explain about 56% of the variance of role-playing and two variables of meeting food needs and export ability.